Unusual bilateral dentigerous cysts in a nonsyndromic patient assessed by cone beam computed tomography - Thais Sumie Imada; V. Tieghi Neto; G. F. Bernini; P. S Silva Santos; I. R. F. Rubira-Bullen; D. Bravo-Calderon; D. T. Oliveira; E. S. Goncales (Wolters Kluwer Medknow Publications, 2014)
In the absence of syndromes, bilateral dentigerous cysts (DC) located on the jaws are unusual. In English based language literature review, we only found eight reports of nonsyndromic bilateral dentigerous cyst associated with mandibular third molars. Therefore, we report the unusual occurrence of sizable nonsyndromic bilateral DC associated with mandibular impacted third molars in a 42-year-old Caucasian woman. The lesions were assessed by cone beam computed tomography (CBCT) the right lesion showed approximately 23.64 mm and the left one, 16.57 mm diameter, both located intimately next to the mandibular canal. Bilateral surgical enucleation, related teeth excision of both third molars and plate for fixation placement on the right and bigger lesion, under general anesthesia was the final treatment choice. Clinical, radiographic and histopathological features confirmed diagnose of bilateral dentigerous cyst. Now-a-days, the patient is on 18 months radiograph follow-up with favorable osseous formation with no evidence of recurrence of the cysts.